The discovery of a novel series of benzimidazoles as a new prospective class of ocular hypotensive agents / Adrian Julian Marcus - Marcus, Adrian Julian (2019)
Ocular hypertension is believed to be involved in the etiology of primary open-angle glaucoma. Although many pharmaceutical agents have been shown to be effective for the reduction of intraocular pressure (IOP), a significant opportunity to improve glaucoma treatments remains. The aims of this study is to discover novel IOP lowering agents and thus, a total of 27 imidazo[1,2-a]- and pyrimido[1,2a]benzimidazole compounds were screened for their IOP lowering activity in ocular normotensive and hypertensive rats. IOP lowering activity was determined by assessing maximum IOP decrease from baseline and control, duration of activities and area under the curve (AUC). During initial screening of 27 compounds, four compounds (RU-551, RU-555, RU-839), and RU-615 showed significant IOP lowering activities in ocular normotensive rats. Further screening for those four compounds was carried out in a single dose application in dexamethasone-induced ocular hypertensive rat and among the four compounds RU-615 was the most active in lowering IOP. RU-615 was similarly tested for dose-response relationship at 3 different concentrations (0.1%, 0.2% and 0.4%) in ocular hypertensive rats and this was followed by evaluation of ocular hypotensive effect after bilateral multiple drop administration with minimally effective concentration for 3-weeks. At the end of the 3-weeks chronic treatment, rats were subjected for retrograde labelling of retinal ganglion cells (RGC) to assess the effect of RU-615 on RGC survival and on retinal antioxidant markers. Both studies demonstrated the ability of RU-615 in providing antioxidant protection and preventing further retinal damages. In vitro part of this study explored the rho-kinase inhibitory activity of RU-615 using dexamethasonetreated HTMC as possible mechanism of action of its IOP lowering activity. Cell viability and CC50 showed that RU615 has a very good safety profile at 1 mM concentration, HTMC viability was slightly under 80%. The rho-kinase inhibitory activity of RU-615 was also compared with the effects of reference rho-kinase inhibitor compound, Y-27632. However, this study didn’t show conventional rhokinase inhibition by RU-615. For conclusion, RU-615, a novel N9imidazobenzimidazole derivatives, exhibits significant IOP lowering effect in both ocular normotensive and ocular hypertensive rats. This IOP lowering activity together with antioxidant properties might be the factors that contributed to prevention of further RGC loss. It is noteworthy, that benzimidazoles have been shown to possess cholinomimetic, carbonic anhydrase inhibitory and adenosine A1 receptor agonist activities. Therefore, in the future studies it is important to identify the upstream targeted receptors for RU-615 and then delineate the involved intracellular signalling pathways which are likely to be other than rho-kinase inhibition.